2014
DOI: 10.1016/j.jacc.2013.09.073
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Statin Medications and Mortality, Major Adverse Cardiovascular Event, and Amputation-Free Survival in Patients With Critical Limb Ischemia

Abstract: Objectives To determine the associations between statin use and major adverse cardiovascular and cerebrovascular events (MACCE) and amputation-free survival in critical limb ischemia (CLI) patients. Background CLI is an advanced form of peripheral arterial disease (PAD) associated with nonhealing arterial ulcers and high rates of MACCE and major amputation. While statin medications are recommended for secondary prevention in PAD, their effectiveness in CLI is uncertain. Methods We reviewed 380 CLI patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
4
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(136 citation statements)
references
References 38 publications
7
113
4
12
Order By: Relevance
“…Recent study demonstrated the protective role of statins in patients with PAD. 33, 34 Although similar results were found in the present study, statins may be prescribed for patients who had a favorable nutritional status. Further study is needed to reveal the beneficial role of statins on the nutritional status.…”
Section: Malnutrition and Sarcopeniasupporting
confidence: 87%
“…Recent study demonstrated the protective role of statins in patients with PAD. 33, 34 Although similar results were found in the present study, statins may be prescribed for patients who had a favorable nutritional status. Further study is needed to reveal the beneficial role of statins on the nutritional status.…”
Section: Malnutrition and Sarcopeniasupporting
confidence: 87%
“…Although there are a number of studies showing improved survival in patients on statins after vascular surgical procedures [14][15][16][17][18]21 or in those with a diagnosis of PAD, 10 there are a few that included only patients with peripheral revascularization procedures. [11][12][13][14][15] Only three of these studies showed survival benefit. [13][14][15] Schanzer et al reported a survival benefit at 1 year (86% vs 81%) with statins in their cohort of patients with CLI who participated in the PREVENT III trial.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac death was defined as mortality due to a heart-related cause (death attributable to ACS, heart failure, arrhythmia, or sudden cardiac death) (Muhlestein et al 2014). Stroke was defined as typical symptoms or signs of remaining neurological deficit lasting > 24 hours with computed tomography or magnetic resonance imaging evidence of cerebral ischemic infarct or intracerebral hemorrhage (Westin et al 2014).…”
Section: Study Outcomesmentioning
confidence: 99%